Validation of model-based estimates (synthetic estimates) of the prevalence of risk factors for coronary heart disease for wards in England. - Scarborough, P; Allender, S; Rayner, M; Goldacre, M (2009)
Several sets of model-based estimates (synthetic estimates) of the prevalence of risk factors for coronary heart disease for small areas in England have been developed. These have been used in policy documents to indicate which areas are in need of intervention. In general, these models have not been subjected to validity assessment. This paper describes a validity assessment of 16 sets of synthetic estimates, by comparison of the models with national, regional and local survey-based estimates, and local mortality rate estimates. Model-based estimates of the prevalence of smoking, low fruit and vegetable consumption, obesity, hypertension and raised cholesterol are found to be valid.